Associations between Facial Emotion Recognition and Mental Health in Early Adolescence - Simcock, Gabrielle (Int J Environ Res Public Health, 2020)
Research shows that adolescents with mental illnesses have a bias for processing negative facial emotions, and this may play a role in impaired social functioning that often co-exists with a mental health diagnosis. This study examined associations between psychological and somatic problems and facial emotion recognition in early adolescence; as any processing biases in this age-group may be an early indicator of later mental illnesses. A community sample of 40 12-year-olds self-rated their symptoms of anxiety, depression, and somatization via two mental health screeners. They also completed a computerized emotion recognition task in which they identified photographs of 40 faces showing expressions of anger, fear, sadness, happiness, or neutral expression. Results showed that increased symptoms of anxiety, depression, and somatization were significantly associated with fewer correct responses to angry expressions. These symptoms were also associated with faster and more accurate recognition of fearful expressions. However, there was no association between mental health and recognition of sad affect. Finally, increased psychological and/or somatic symptomology was also associated with better identification of neutral expressions. In conclusion, youth with increased psychological and/or somatic problems exhibited a processing bias for negative anger and fear expressions, but not sadness. They showed better processing of neutral faces than youth with fewer psychological and/or somatic problems. Findings are discussed in relation to indicators of mental illnesses in early adolescence and the potential underpinning neural mechanisms associated with mental health and emotional facial recognition.